Towards a health-aware fault tolerant control of complex systems: A vehicle fleet case - Lipiec, Bogdan; Mrugalski, Marcin; Witczak, Marcin; Stetter, Ralf (Zielona Góra: Uniwersytet Zielonogórski)
The paper deals with the problem of health-aware fault-tolerant control of a vehicle fleet. In particular, the development process starts with providing the description of the process along with a suitable Internet-of-Things platform, which enables appropriate communication within the vehicle fleet. It also indicates the transportation tasks to the designated drivers and makes it possible to measure their realization times. The second stage pertains to the description of the analytical model of the transportation system, which is obtained with the max-plus algebra.
Keywords: FTCD; modeling bearings degradation; remaining useful life prediction; health-aware fault tolerant control; Takagi-Sugeno model